MEMBANGUN QUALITY TIME ORANG TUA DENGAN ANAK USIA 4-6 TAHUN DI KOTA MALANG - Damayanti, Ervina; Elvira, Melly (Jurnal Penelitian Anak Usia Dini, 2024)
Quality time is time spent together with full focus on children, creating emotional bonds, and strengthening family relationships. This involves activities that not only fill time, but also add value to the child's development and create positive memories. This research aims to describe the quality time of parents with children aged 4-6 years in Malang City. The research method uses a quantitative approach with a survey research type with a sample of 253 parents in Malang City who have children aged 4-6 years. Data collection uses questionnaire techniques. Data analysis uses descriptive data analysis. The results of this study show that the majority of parents spend quality time with their children well. With an average percentage of 86% which is included in the "high" category. This shows that the majority of parents in the Malang City area understand the importance of quality time and implement it effectively in daily interactions with their children. Parents in Malang City generally have a good understanding of the concept of quality time, which includes time spent with children attentively and without distractions. Based on the problem formulation, it shows that parents in Malang City spend quality time well. This research also shows that parents' quality time with early childhood children can have a positive impact on aspects of child development. Overall, parents in Malang City do more quality time activities by participating in events at their children's schools. The reason parents carry out these activities may be that many parents have busy work schedules and they realize that school events are the right time to spend time with their children without disturbing their daily routine.